PELAJARAN DARI KASUS SISTEM BAGI HASIL PENGELOLAAN LAHAN KELAPA SAWIT ANTARA PETANI DENGAN PERUSAHAAN DI DESA MSPN - Loso Judijanto (Adpertens: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyse oil palm land management in MSPN Village, focusing on the profit-sharing system implemented between farmers and the company. The main issue addressed is the dissatisfaction felt by farmers, who perceive an imbalance in the distribution of profits between the two parties, as well as the impact on farmer welfare and environmental sustainability. The objective of this research is to evaluate the effectiveness of the profit-sharing system in oil palm land management and to provide recommendations for reducing potential problems and improving farmer welfare. The methodology employed is a qualitative approach, utilising interviews with farmers and company representatives, as well as document analysis of profit-sharing agreements. The results indicate that there is room for improvement in the profit-sharing arrangement to enhance the welfare of plasma farmers better, thereby preventing potential issues such as decreased farmer motivation and unsustainable plantation operations. Recommendations include improving communication among parties, revising the profit-sharing agreements, and increasing training for farmers on more environmentally friendly land management practices.